2017
DOI: 10.3389/fimmu.2017.00456
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TLR4 in Non-Small Cell Lung Cancer Is Associated with PD-L1 and Poor Prognosis in Patients Receiving Pulmonectomy

Abstract: Currently, the effect of inflammation on tumorigenesis and progression has been widely noted. As a member of pattern recognition receptors, toll-like receptor 4 (TLR4) plays a pivotal role in tumor immune microenvironment and has been increasingly investigated. In the present study, we evaluated TLR4 expression and its association with programmed cell death ligand 1 (PD-L1) in non-small cell lung cancer (NSCLC) tissues and assessed the predicting value of TLR4 on postoperative outcome. A total of 126 NSCLC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 56 publications
7
43
0
Order By: Relevance
“…Consistent with this finding, there is a positive correlation between TLR4 and PD‐L1 expression in tumors . In addition, elevated TLR4 expression is associated with poor survival of cancer patients . Thus, DAMP‐mediated upregulation of PD‐L1 expression could contribute to the downregulation of immune activity during radiotherapy and DNA damage‐dependent chemotherapy.…”
Section: An Immune Response Mediated By Cell Death Signal After Dna Dsupporting
confidence: 61%
See 3 more Smart Citations
“…Consistent with this finding, there is a positive correlation between TLR4 and PD‐L1 expression in tumors . In addition, elevated TLR4 expression is associated with poor survival of cancer patients . Thus, DAMP‐mediated upregulation of PD‐L1 expression could contribute to the downregulation of immune activity during radiotherapy and DNA damage‐dependent chemotherapy.…”
Section: An Immune Response Mediated By Cell Death Signal After Dna Dsupporting
confidence: 61%
“…While DAMPs stimulate immune activity, leading to further cancer cell‐killing, HMGB1‐mediated TLR4/MyD88/TRIF signaling upregulates PD‐L1 expression in surrounding viable cancer cells . Consistent with this finding, there is a positive correlation between TLR4 and PD‐L1 expression in tumors . In addition, elevated TLR4 expression is associated with poor survival of cancer patients .…”
Section: An Immune Response Mediated By Cell Death Signal After Dna Dmentioning
confidence: 53%
See 2 more Smart Citations
“…In this study, we established TLR4/MYD88/STAT3 and TLR4/TRIF/STAT3 pathways in melanoma and demonstrated their pathogenic roles. TLR4 expression and constitutive STAT3 activation are also found in other cancers, such as liver 52 , lung 53,54 , and stomach cancers 55 .…”
Section: Discussionmentioning
confidence: 98%